Prevalence and associated risk factors of Intestinal parasites in rural high-mountain communities of the Valle del Cauca-Colombia. - Magda Gileydi Peña-Quistial; Javier Antonio Benavides-Montaño; Nestor Javier Roncancio Duque; Gerardo Alejandro Benavides-Montaño (Public Library of Science (PLoS), 2020)
The aim of this study was to measure the prevalence of gastrointestinal parasites (GI) in domestic animals and children in high mountain populations in the districts of Combia and Toche, Valle del Cauca-Colombia. These communities have been affected by the armed conflict in Colombia and are susceptible to health risk factors related to the Colombian post-conflict. Prevalence and risk factors were measured using Bayesian methods on 45 structured interviews applied to 29 families in Combia and 16 in Toche. This inquire aimed to analyze the socio-economic and demographic factors associated with the presence of parasites. This interview was conducted with 50 children: 40 (80%) from Rita Sabogal school district of Toche, and 10 (20%) from Tablones-Atanasio Girardot schools. 23 faecal samples from asymtomatic children from these schools were collected. Subsequently, 308 animals were characterized through the analysis of 64 faecal samples from asymptomatic individuals (20,8%); 18/41 from dogs (43,9%), 18/175 from poultry (10,3%), 7/13 from cats 56,84%, 6/20 from equines (30%) and from 15/59 cattle (25,43%). The prevalence of intestinal parasites among children under six years was 60% [95% PI = 41%-78%]; Endolimax nana, 24% [95% PI = 9,8%-42%]; Iodamoeba buetschlii, 16% [95% PI = 4,7%-32%]; Entamoeba coli, 35% [95% PI = 18%-55%]; Giardia lamblia, 12% [95% PI = 2,7%-27%]. In Equids the presence of Strongylus spp was 37% [95% PI = 10%-71%]; Parascaris equorum, 37% [95% PI = 10%-71%]; in dogs, Dipylidium caninum was 20% [95% PI = 6%-39%]; Trichuris trichiura, 9% [95% PI = 1,3%-26%]; Toxocara canis, 25% [95% PI = 9%-46%]; in cats, Toxocara cati had a prevalence of 44% [95% PI = 16%-75%]; cyst of Eimeria spp, 15% [95% PI = 3,4%-33%]; in poultry and Eimeria zuernii in cattle, 50% [95% PI = 23%-77%]. There was no association with exposure of humans to animal parasites. However, we conclude that female and children under 6 years of age are more likely OR (6,72-2,3) to get parasites.